EVALUASI PERMASALAHAN GAS INTERFERENCE PADA ELECTRICAL SUBMERSIBLE PUMP DI SUMUR MD-17 - Hermawan, Bagus Danial; Welayaturromadhona, Welayaturromadhona; Saputri, Eriska Eklezia Dwi; Sari, Riska Laksmita; Abror, Hadziqul (Petro : Jurnal Ilmiah Teknik Perminyakan, 2023)
Natural flow can not be performed in the reservoir from the MD-17 well. The most likely reason is because it is classified as a mature well, so an Artificial Lift is needed. The artificial lifting mechanism used is the Electrical Submersible Pump. In this research, the writer analyze the problem of "Gassy" condition or interference. The MD-17 well problem shows that the free gas in this well is 245.213 mscf. Moreover, the amount of free gas that enters the Pump is 8%. From these problems, it causes ESP become disrupted and not produce optimally. The solution to the gas interference problem at the MD-17 Well is the bleed off method and using Advance Gas Handling. The first method is with bleed off method for improve ESP performance so that production will be stable. Then the second method of handling gas interference is by using Advance Gas Handling. From the data analysis and calculation with the formula for AGH, it can produce efficiency in dealing with Gas Interference, so can produce 64.4 mscf of gas from Pump Intake and then can increasing production.